Structural, optical and electrical properties of sol-gel derived titanium dioxide thin film - (:unkn) unknown (AMER INST PHYSICS, 2007)
Optical, structural and electrical (dc and ac) properties of sol-gel derived TiO2 film in a wide range of temperature (290 - 652 K) were investigated. XRD analysis was used for investigation the crystallinity of the films. Optical bad gap of the film were determined from transmission spectra. With the examination of the impedance spectra clear differences could be seen in the dependence of omega on both real and imaginary part of impedance between 290 K and 652 K. The impedance response is significantly changed with the increase of temperature.
Keywords: sol-gel; anatase; impedance spectroscopy; XRD